Neuroprotective Effects of Trolox, Human Chorionic Gonadotropin, and Carnosic Acid on Hippocampal Neurodegeneration After Ischemia-reperfusion Injury - Babahajian, Asrin; Sarveazad, Arash; Golab, Fereshteh; Vahabzadeh, Gelareh; Alizadeh, Akram; Rasoolijazi, Homa; Amini, Naser; Entezari, Maedeh; Soleimani, Mansoureh; Katebi, Majid; Haramshahi, Seyed M. A. (Current Stem Cell Research & Therapy, 2019)
Introduction: One of the serious complications of stroke is memory impairment, which is considered as one of the complications of reperfusion of tissue. The present study was designed to compare the effect of administration of Trolox, carnosic acid and Human Chorionic Gonadotropin (HCG) immediately after reperfusion of the stroke tissue on the memory and hippocampal histology. Method: Ischemia-Reperfusion Model (IRI) was created by bilateral occlusion of the common carotid artery for 15 minutes and the first dose was administered immediately after reperfusion. 10 days after ischemia, passive avoidance memory test and apoptotic protein levels were evaluated. Results: Cerebral Ischemia perfusion reduced the time of latency in entering the dark box in the ischemic group. Administration of Trolox and HCG increased this latency time, while treatment with carnosic acid had no effect. Also, IRI significantly reduced the number of healthy cells in the hippocampus. Administration of Trolox, carnosic acid and HCG increased the number of healthy cells and decreased the expression of Caspase-3 and Bax, but significantly increased the expression of Bcl-2 compared to the ischemic group. Conclusion: Findings indicate the beneficial effects of HCG and Trolox on the improvement of memory and the number of healthy cells in the hippocampal region. It is worth noting that the amount of apoptosis in the hippocampus was significantly reduced by Trolox, HCG and Carnosic acid.
Keywords: Ischemia